Immunohistochemical heterogeneity of nerve cells in the human adrenal gland with special reference to substance P - Colombo-Benkmann, Mario; Klimaschewski, Lars Peter; Heym, Christine (Journal of histochemistry & cytochemistry, 1996)
Neurons in the human adrenal medulla, stained by the NADH-diaphorase reaction, were counted and their neurochemical markers were investigated by double labeling immunofluorescence with special reference to substance P. The findings indicate a significant participation of intramedullary nerve cell bodies in human adrenal innervation with 40.4 neurons/mm3 adrenal medulla. Substance P-immunoreactive neurons, which made up approximately 20% of all neurons, exhibited heterogeneity by co-localization of immunoreactivities for dynorphin, for cholecystokinin, and for neurofilament triplet. Substance-P-immunolabeled neurons were always nonreactive for calcitonin gene-related peptide, for vasoactive intestinal polypeptide, or for tyrosine hydroxylase, the rate-limiting enzyme of catecholamine synthesis. These chemical phenotypes of intramedullary neurons reveal immunohistochemical similarities with postganglionic neurons in parasympathetic ganglia or with enteric neurons, suggesting a hitherto unrecognized functional significance of the intrinsic nervous system in the human adrenal gland.
Gesehen am 06.11.2025